The Internal Audit Function and Its Effect on Audit Quality - Muhammad Iqbal Ramadhan; Laras Auditria Putri (Budapest International Research and Critics University, 2022)
This research aims to see the internal audit function and its effect on audit quality. This research uses quantitative research. The research data used in this study consisted of All Non-Financial Companies listed on the Indonesia Stock Exchange. After applying the sample selection criteria, finally 722 observations were obtained as the main sample in this study. This study uses multiple linear regression for analysis techniques with STATA 14.0 software. The results show that internal audit size has a positive and significant effect on audit quality as measure by earning management. Internal audit expertize has a positive and significant effect on audit quality as measure by earning management. Internal audit certification has a positive and insignificant effect on audit quality as measure by earning management.